Customer Loyalty Programs and Marketing Strategies - Ramesh, H. N. (Indian Journal of Marketing, 2011)
This article focuses on history of customer loyalty, its impact on marketing, and also the influence of various factors on customer loyalty. More importantly, the article analyses the customer satisfaction, customer value and customer loyalty so as to identify the market segments based on loyalty and value factors rather than only on economic factors. The article also focuses on the classification of customers on the basis of loyalty. The typical customer loyalty programs used by the companies are also discussed in the article.